Problems of Educational Wastage In Primary Level Education of Nepal: Some Suggestions to Reduce It - Hada, Bhupendra (Tribhuvan University Journal, 2010)
This paper presents the problems of wastage in education during 2006-08 at the primary level, in terms of repetition and dropout. The main objectives of this paper is to enumerate the reasons of repetition and dropout of students at primary school education, because they are the major barriers and stumbling block for the school education system of every country, and they also enhance to decrease internal efficiency of education system. Promotion, repetition and dropout are the prominent indicators of internal efficiency. If the repetition and dropout rates are high, promotion rate will be low, and it indicates the low internal efficiency of the primary school education. There are many causal factors for educational wastage and they are explained in brief. Hence, the table and the figure available from DOE are used to analyze the sources of educational wastage in primary level education. The conclusions and recommendations are put forward for reducing educational wastage to minimum in the Nepalese context.